Multiple Candidacies and the Role of the Lowest Electoral Tier for Individualized Campaigning. (November 2015) - Chiru, Mihail
The effects of mixed electoral systems on politicians' incentives and work in the legislature are most often studied in isolation from the possibly mediating role of campaign behavior. The tier in which a candidate runs might determine a particular style and content of campaigning, more or less party centered and more or less constituency oriented, which in turn could shape how the elected politician will perceive her mandate and act upon it. But what type of campaigning prevails when candidacy in multiple tiers is the rule and the majoritarian element is the dominant component of the mixed electoral system? The present study draws on a survey of 431 candidates in the 2010 Hungarian parliamentary elections and uses linear, logistic regressions and marginal effects to estimate the effect of the above-mentioned electoral system characteristics as well as of organizational and career attributes on campaign norm, constituency-related agenda, and independent campaigning. What appears to matter the most for the degree of campaign individualization is the lowest electoral tier in which the candidate runs, irrespective of her electoral security. The study also reveals the significant effects of two dimensions previously ignored by the literature: the level of nomination and the local politics profile (years of experience and the prospect of holding a dual mandate).